Sampling Strategies for Assessing Male Clients of Female Sex Workers in Public Health Research: A Compilation of Global Evidence. - Banerjee, Sitikantha; Bandyopadhyay, Kajari; Chakraborty, Debjit; Bhatta, Mihir (AIDS & Behavior, 2025)
Clients of Female Sex Workers (FSWs) are major bridge population in HIV transmission. Any research among them remains challenging because they are hidden within society. The objective of this review was tocompile the global evidence on different sampling strategies used to access male clients of female sex workers for research purpose, the challenges faced during the sampling process andpossible sources of bias. Original articles and reports published globally in last 10 years, in English language and those with full text freely available online were included in this scoping review. A comprehensive search was carried out among the electronic peer-reviewed literature database (Pubmed and Web of Science) using a pre-designed peer reviewed search strategy. Narrative synthesis was applied out across all such articles. A total of 36 articles were finally included in this review. The common sampling techniques used include convenience sampling, referral by FSWs/ pimp/brothel manager/clients, time location cluster sampling, use of virtual network, anonymous telephone survey, referred by clinicians of STI clinic etc. Overall response rate varied between 35 and 90%. Major challenges in participant recruitment included non-response, feasibility issue specially to cater non-brothel-based clients, safety issue for investigators, over-representation of clients with lower socio-economic status, higher refusal rate for known HIV positive clients to provide biological sample etc. As different sampling techniques have comparable response rate, it can be recommended that a pilot study should be carried out in local context to finalise appropriate participant recruitment technique for a given population.